A privacy protection mechanism for numerical control information in Internet of things. (August 2017) - Li, Yunfa; Li, Mingyi
The application of numerical control machine tool in the Internet of things has attracted large number of attention. It is a complex network system that integrates sensor network, Internet, and mobile communication network. However, some security issues have not been solved by Internet security technology. In order to enhance the security of system, we, respectively, propose a lightweight authentication method for wireless sensor networks and an Internet data privacy protection strategy based on organizational characteristics of computerized numerical control machine tool and the numerical control information transmission mode in Internet of things. The two methods constitute a privacy protection mechanism for numerical control information in Internet of things. In order to show the effectiveness of the privacy protection mechanisms, series of analysis about safety is presented. Analysis results show that this mechanism can ensure the security of information and the privacy of the numerical control machine tool in Internet of things.